1986
DOI: 10.1051/forest:19860304
|View full text |Cite
|
Sign up to set email alerts
|

Dormance des bourgeons apicaux du frêne (Fraxinus excelsior L.) : évaluation du pool des nucléosides triphosphates et éventail des températures actives sur le débourrement des bourgeons en période de dormance

Abstract: Nous proposons une technique biochimique nouvelle basée sur les modifications de la régulation de l'énergétique cellulaire, en rapport avec l'état de dormance. L'analyse consiste à mesurer l'aptitude du matériel végétal à augmenter sa teneur en nucléosides tri-phosphates non adényliques (NTP) à la suite de l'apport d'un précurseur exogène de l'ATP, l'adénosine. Les résultats de cette étude sont que les conceptions de V EC ts, pour la première fois, sont dévcloppécs biochimiquement. Les optimums de température … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The relatively longer resting period of the seedlings from stored seed may be responsible for the reduction of their final shoot height. For many authors, growth inhibition is related to the metabolism regulation and to the mechanisms of transport of nutrient [5,11,12,43]. In Castanea sativa, the diffusion of the acid 5,5′ -dimethyloxazolidin 2,4-dione (DMO) and its accumulation in the meristematic zone of the apical bud favoured shoot elongation [43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relatively longer resting period of the seedlings from stored seed may be responsible for the reduction of their final shoot height. For many authors, growth inhibition is related to the metabolism regulation and to the mechanisms of transport of nutrient [5,11,12,43]. In Castanea sativa, the diffusion of the acid 5,5′ -dimethyloxazolidin 2,4-dione (DMO) and its accumulation in the meristematic zone of the apical bud favoured shoot elongation [43].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the effect of parental tree on the final shoot height appears to be dependent on the seed physiological status (fresh or stored). Even though there were small differences between parental trees in the case of fresh seeds, the variability in height among parental trees increased with the duration of seed storage ( 12 were large, they produced the shortest seedlings after 6 months of storage. For the final number of leaves, however, no significant differences were observed among parental trees as a consequence of a large variability within the population of seedlings originating from the each individual.…”
Section: Seedling Growth and Number Of Leavesmentioning
confidence: 99%
“…In Jerusalem artichoke tubers, Gendraud (1975) showed that the metabolic level of NTPs is a good dormancy marker; unlike a growing bud, a dormant bud is unable to use an exogenous supply of adenosine to increase the NTP content. This correlation permits the characterization of endodormancy in various tree species (Lavarenne et al 1982;Barnola et al 1986;Balandier et al 1993).…”
Section: Dormancy Is Observed In Many Plants In Temperate Zonesmentioning
confidence: 99%